The Neutralizing Effect of Squeezed Juice, Infusion and Ethanol Extract of Miana Leaves - Isnayanti Isnayanti; Ira Asmaliani; Nurlina Nurlina; Mirawati Mirawati (Universitas Muslim Indonesia, 2023)
The traditional use of miana leaves as a remedy for various ailments, including stomach acid, is well-documented. The utilization of traditional treatments is prevalent due to the absence of side effects associated with synthetic chemical treatments. The consumption of miana leaves by communities is typically achieved through the ingestion of the juice extracted from fresh leaves or by boiling the leaves in water. The purpose of this study is to investigate the mechanism of action of miana leaves as a stomach acid remedy, specifically, its neutralizing effect on stomach acid. The study was conducted on water extracts using squeezed juice and infusion methods, as well as ethanol extracts using the maceration method. The dosage used was obtained by converting the commonly used dosage by the community, which is 3 medium-sized leaves. The average weight of 1 fresh leaf is 1g and the volume of medicine consumed is 1 tablespoon or 15 mL. The concentration for squeezed juice is 20%, infusion 2.08% and ethanol extract 0.28%. The results obtained from maceration, infusion, and miana leaf extract demonstrate a neutralization capacity of 26.617 ± 0.236; 26.7 ± 0.05 and 26.633 ± 0.07 respectively. In conclusion, this study demonstrates that miana leaves possess a neutralizing effect on stomach acid, and may be used as a remedy for stomach acid.